Tutorial: Create Rich Mobile Apps on Touch Devices - Tillmann, Nikolai; Moskal, Michal; Halleux, Jonathan "Peli" de; Burckhardt, Sebastian; Ball, Thomas; Bishop, Judith (Proceedings of the First International Conference on Mobile Software Engineering and Systems (MOBILESOFT), 2014)
We are experiencing a technology shift: Powerful and easy-to-use mobile devices like smartphones and tablets are becoming more prevalent than traditional PCs and laptops. Mobile devices are going to be the first and, in less developed countries, possibly the only computing devices which virtually all people will own and carry with them at all times. In this tutorial, participants will learn about developing software directly on their mobile devices. The tutorial is based on TouchDevelop, a modern software development environment that embraces this new reality, treating mobile devices as first-class software development machines, instead of relying on legacy development models built around PC. TouchDevelop comes with typed, structured programming language that is built around the idea of only using a touchscreen as the input device to author code. Access to the cloud, flexible user interfaces, and access to sensors such as accelerometer and GPS are available as a first-class citizens in the programming language. TouchDevelop is available as a web app on Windows tablets, iOS, Android, Windows PCs and Macs, and as a native app on Windows Phone.
Tutorial